PEMANFAATAN CHROMEBOOK SEBAGAI PENUNJANG PEMBELAJARAN AKTIVITAS KEBUGARAN UNTUK KESEHATAN - Nuraini, Nisrina; Dirgantoro, Edwin Wahyu; Rakhman, Arie (Universitas Negeri Medan, 2025)
The purpose of this study is to see the usefulness of chromebooks as a learning support for fitness activities for health reviewed from the responses of teachers and students. The method used was quantitative descriptive with the population of class VIII of SMPN 1 Hulu Sungai Tengah and PJOK teachers, a sample of class VIII E of 25 students and 1 teacher. The research instruments included teacher observation, student questionnaires, and student question tests. The results of the analysis showed that the use of Chromebooks gave positive results, as seen from the observation of students' attitudes (activeness, interest, seriousness) that were very high, as well as effective and efficient indicators that were also very high, indicating that students were able to accept and respond to learning fitness activities for health quickly. The response to the students' questionnaire showed 54% of the high category, and the average test score increased from 75.6 to 88.4 (an increase of 16.93%). From the results of the data, it can be concluded that the use of chromebooks as a learning support is very helpful in the fitness learning process for health.